Sosialisasi dan Pelatihan Pengawasan Pekerjaan Jalan Bagi Perangkat Desa di Kecamatan Tangen Kabupaten Sragen - Asri Nurdiana (Jurnal Pengabdian Vokasi, 2023)
Infrastructure is one factor that directly influences the operations of a region. The Sragen Regency Government annually repairs and constructs roads spread across 20 sub-districts. In 2023, as many as 28 roads and 4 bridges in Sragen Regency will be repaired and built. In the future implementation of the project must refer to procedures and regulations so that it will produce infrastructure with good quality. Currently, the condition of the people in the village does not yet know and understand the procedures for supervising road works in accordance with the technical specifications issued by the Ministry. So it is feared that later it can affect the quality of the work. Therefore, assistance is needed regarding the procedures for carrying out road works starting from planning the RAB to supervising road works that refer to applicable standards and regulations.